2019
DOI: 10.15296/ijwhr.2020.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Warm Compress Bi-stage on Pain Strength in Labor Stages and After Delivery

Abstract: Objectives: Perineal warm packs with an increase in subcutaneous temperature and the stimulation of cutaneous receptors are advocated in the belief of pain and probably increase comfort during labor and delivery. This study aimed to investigate the effectiveness of warm compress bi-stage on pain strength in the first two stages of labor and after delivery in primiparous women. Materials and Methods: This study was a randomized clinical trial that was conducted in Shiraz hospitals from July 2012 to March 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Other studies have shown that in addition to educational protocols, complementary medicine, including pressure medicine, compresses, and herbal remedies, is also effective in reducing pain and anxiety in women's problems. [ 25 26 27 28 29 30 31 32 33 ] The present study findings revealed a significant decrease in postoperative pain in the intervention group compared to the control group. In fact, the interventions and consultation services that aimed at reduction of the patients’ psychological load prior to cesarean section resulted in better acceptance of the process of operation and the following period.…”
Section: Discussionmentioning
confidence: 47%
“…Other studies have shown that in addition to educational protocols, complementary medicine, including pressure medicine, compresses, and herbal remedies, is also effective in reducing pain and anxiety in women's problems. [ 25 26 27 28 29 30 31 32 33 ] The present study findings revealed a significant decrease in postoperative pain in the intervention group compared to the control group. In fact, the interventions and consultation services that aimed at reduction of the patients’ psychological load prior to cesarean section resulted in better acceptance of the process of operation and the following period.…”
Section: Discussionmentioning
confidence: 47%
“…The sample sizes of the studies ranged from 28 to 137. Out of 10 included studies, five 22 , 25 , 28 , 30 , 34 were performed in Iran, and the remaining five were from Taiwan 35 , Brazil 36 , India 26 , Australia 24 , and Spain 27 . The age of the participants ranged from 18 to 35 years ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the review, they included randomized controlled trials (RCTs), quasi-RCTs, even cluster studies, even available abstracts only, and trials with sequential intervention 20 of cold and hot applications. Furthermore, few trials were missed 24 , 25 , and few got published after this Cochrane review publication 26 - 28 . Thus, this systematic review (SR) and meta-analysis (MA) study aimed, keeping in mind sound methodological planning, to provide strong evidence regarding the efficacy of heat therapy.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,9 Then, a warm compress is an action by providing a warm compress that aims to meet the needs of comfort, reduce or relieve pain, reduce or prevent muscle spasms and provide a feeling of warmth. [10][11][12] Combined therapy between and CPM and warm compresses uses the principle of a warm sensation and a relaxation inducer which has been shown to reduce pain during the 1st stage of labor. 13,14 caused by pressure can be resolved.…”
Section: Discussionmentioning
confidence: 99%